Two-dimensional C20-based monolayers and heterostructures for photocatalytic overall water splitting - Miao Liu; Chuan-Lu Yang; Xiaohu Li; Li-Bo Zhan; Yongqing Li (npj 2D Materials and Applications)
Abstract C20, as the smallest carbon cage, possesses unique properties but has not been extensively explored for photocatalytic overall water splitting. This study proposes three two-dimensional (2D) C20-based monolayers (α-C20, β-C20, and γ-C20) as potential photocatalysts for efficient water splitting with direct Z-scheme. α-C20 monolayer has ideal band edges for hydrogen evolution reaction (HER) with a Gibbs free energy of 0.0147 eV. GeS2/α-C20, MoS2/β-C20, SnS2/β-C20, and SnSSe/β-C20 heterostructures are developed. However, γ-C20-based heterostructures did not meet the Z-scheme requirements. Notably, the solar-to-hydrogen (STH) efficiency for the SnSSe/β-C20 heterostructure can reach 27.54%. The favorable Gibbs free energies indicate that both HER and oxygen evolution reaction (OER) can occur spontaneously within suitable pH ranges. Nonadiabatic molecular dynamics simulations show that the lifetimes of photoexcited carriers in the GeS2/α-C20 heterostructure are in the nanosecond range, suggesting robust photocatalytic activity. These results offer valuable insights into the potential of C20-based photocatalysts for water-splitting applications.